Cover Image, Volume 42, Issue 1. Issue 1 (12th January 2022) - Tan, Laura Ling Ying; Le, Quynh‐Thu; Lee, Nancy Ying Ying; Chua, Melvin Lee Kiang
Abstract : The cover image is based on the Discussion of Paper JUPITER‐02 trial: advancing survival for recurrent metastatic nasopharyngeal carcinoma and next steps by Melvin Chua et al., https://doi.org/10.1002/cac2.12248 .